Geographic Proximity And Firm Innovation: Evidence From The Chinese Manufacturing Industry - Ruan, Zhao; Yue, Su; Jia, Xinlin (Migration Letters, 2024)
Innovation, competitive advantage, and firm performance are all positively affected by knowledge-sharing techniques. We consider the geographic proximity to research institutes as a proxy of the efficiency of knowledge sharing. We examine how and to what degree the practice of knowledge-sharing influences businesses’ innovation using a sample of Chinese manufacturing companies chosen between 2009 and 2021. Thus, the relationship between corporate innovation and closeness to research institutions is investigated experimentally in this study. The decisive findings indicate that a company’s ability to innovate is strongly impacted by its proximity to research institutions, which suggests that proximity may also lower coordination costs and enhance information flow efficiency. Additionally, this research reveals that institutions with a STEM (science, technology, engineering, and mathematics) concentration have a stronger correlation with information sharing and entrepreneurial innovation in the manufacturing sector. Furthermore, under similar conditions, the positive effect for non-SOEs and firms with lower R&D expenditures is more critical for firms close to research institutions. We find consistent evidence for a battery of robustness checks. Overall, the study provides insightful implications that university and research center clustering is advantageous for generating and exchanging necessary knowledge.